(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This work analyzes the dialectics of the interdependence of the economy and the ethics of the organization of labor and moral principles and norms of the attitude of social groups of society to the problems of ecology, in various forms of its manifestation. We are talking, first of all, about such varieties of ecology, considered through the prism of economic processes, such as social ecology, environmental ethics and bioethics, affecting the natural, biological and social levels and forms of development of the material world (matter). From the perspective of this study, the author examines the specificity and difference in the manifestation, in market relations, of the organization of labor, on the one hand, and the influence of the economy on work ethics, considered through the prism of the impact of production on the ecological state of the environment and its inhabitants, from among the flora and fauna , and the person himself (society) in states, differing in the level of their economic development, on the other hand. In this regard, in the context of solving the problems of the correlation and mutual influence of the economy and the environment in the context of globalization, an analysis is given of the differences in the formation and development of capitalism, as a socio-political system, relatively developed, post-information, and developing, raw-material-dependent countries of the world.